The TAIGA experiment : From cosmic ray to gamma-ray astronomy in the Tunka valley - Budnev, N.; Astapov, I.; Bezyazeekov, P.; Bogdanov, A.; Boreyko, V.; Büker, M.; Brückner, M.; Chiavassa, A.; Chvalaev, O.; Gress, O.; Gress, T.; Grishin, O.; et al. (Karlsruhe, 2016)
The physical motivations and advantages of the new gamma-observatory TAIGA (Tunka Advanced Instrument for cosmic ray physics and Gamma Astronomy) is presented. The TAIGA array is a complex, hybrid detector for ground-based gamma-ray astronomy for energies from a few TeV to several PeV as well as for cosmic ray studies from 100 TeV to several EeV. The TAIGA will include the wide angle Cherenkov array TAIGA-HiSCORE with ~5 km$^{2}$ area, a net of 16 IACT telescopes (with FOV of about 10x10 degree), muon detectors with a total area of up to 2000-3000 m$^{2}$ and the radio array Tunka-Rex.